2005
DOI: 10.1007/s00268-005-7767-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surgical Techniques for Treatment of Benign Toxic Multinodular Goiter

Abstract: Controversy remains regarding the best surgical approach for toxic multinodular goiter (MNG). The aim of this study was to evaluate the results of various thyroid operations for managing toxic MNG. A group of 100 patients with toxic MNG were divided into three groups and managed with total thyroidectomy (TT; group I, n-17), near-total thyroidectomy (NTT; group II, n = 48), or bilateral subtotal thyroidectomy (BST; group III, n = 35). Patients were compared with regard to age, gender, surgical operations, compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 36 publications
4
29
0
6
Order By: Relevance
“…The study has demonstrated lack of significant difference in the prevalence of hypocalcemia in both groups. Similar data was reported by Alimoglu et al, Bellantone et al and Pappalardo et al (3,12,13). These authors stress the presence of complications following bilateral subtotal thyroid resections.…”
Section: Discussionsupporting
confidence: 84%
“…The study has demonstrated lack of significant difference in the prevalence of hypocalcemia in both groups. Similar data was reported by Alimoglu et al, Bellantone et al and Pappalardo et al (3,12,13). These authors stress the presence of complications following bilateral subtotal thyroid resections.…”
Section: Discussionsupporting
confidence: 84%
“…In another series RLN palsy was reports 5.88% of TT group and 2.85% after STT group 11 . In present study RLN palsy occurred in 5.3% of TT group 2.2% of STT group.…”
Section: Postoperative Hospital Staymentioning
confidence: 81%
“…For the selected cases, the decision for total excision is sometimes taken during surgery due to the absence of macroscopically normal tissue from the thyroid gland; the patient is informed of this possibility preoperatively. Before the 20th century total thyroidectomy was an intervention reserved for cases of thyroid cancer and benign thyroid pathology for rarely because of the high rate of postoperative complications [8]. Currently it is the standard treatment for toxic or non-toxic multinodular goiter.…”
Section: Discussionmentioning
confidence: 99%
“…Permanent hypocalcemia is absent in the present study, it is most often linked to accidental parathyroid removal. The transient hypocalcemia rate is in the range of data in the literature ranging from 1.6% to 20% [8] [9] [11] [12].…”
Section: Discussionmentioning
confidence: 99%